2022
DOI: 10.3390/toxics10110681
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons Induced by Smoking and Air Pollution: Correlation with Oxidative Stress in Chronic Obstructive Pulmonary Disease Patients

Abstract: Oxidative stress is induced by tobacco smoking and is also associated with exposure to air pollution, which are two of the most important risk factors for chronic obstructive pulmonary disease (COPD). The aim of this study was to correlate tobacco use and exposure to air pollution with oxidative stress markers useful in clinical practice in patients with COPD. A total of 102 patients were included and the levels of polycyclic aromatic hydrocarbons (PAHs), malondialdehyde, uric acid and number of packs-years (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…PAHs in biological tissues as human plasma are present because of the important sources of provenience as smoking and occupational exposure [ 25 ]. These compounds are partially metabolized, and the presence in these biological media is not affected by protein binding [ 26 ]. Therefore, the compounds are present in free form, so the determination from these samples is possible as in other types of samples by using solid–liquid extraction using deproteinization, solid-phase extraction, or liquid–liquid extraction [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAHs in biological tissues as human plasma are present because of the important sources of provenience as smoking and occupational exposure [ 25 ]. These compounds are partially metabolized, and the presence in these biological media is not affected by protein binding [ 26 ]. Therefore, the compounds are present in free form, so the determination from these samples is possible as in other types of samples by using solid–liquid extraction using deproteinization, solid-phase extraction, or liquid–liquid extraction [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…PAHs in biological tissues as human plasma are present because of the important sources of provenience as smoking and occupational exposure [25]. These compounds are partially metabolized, and the presence in these biological media is not affected by protein binding [26]. Therefore, the compounds are Second step was wavelength selection of excitation and emission wavelength in order to improve method sensitivity.…”
Section: Methods Developmentmentioning
confidence: 99%
“…Дополняя и усиливая свободнорадикальное и перекисное окисление, упомянутый патологический каскад является связующей нитью в развитии системной сосудистой дисфункции. В специальной литературе активно обсуждается вопрос о связи процессов ремоделирования сосудов малого диаметра в ответ на воздействие табачного дыма с механизмами избыточного фибро-(ОС) [23]. Ткань легких в большом количестве содержит субстрат перекисного окисления липидов -ненасыщенные жирные кислоты, продукты окисления которых стимулируют активность протеинкиназы-С, высвобождение кальция, снижают синтез оксида азота (NO), нарушают эндотелий-зависимую вазодилатацию, дезориентирует механизмы репликации эндотелиальных клеток и ангиогенеза, индуцируют апоптоз.…”
Section: Chapter 2 Role Of Endothelial Dysfunction In Development Of ...unclassified
“…Для изучения особенностей системного и регионального кровотока в ответ на воздействия продуктов никотина в зависимости от средств его доставки были обследованы 45 курящих пациентов без АГ и сердечно-сосудистых заболеваний (22 женщины, 23 мужчины; средний возраст -25 (23)(24)(25)(26)(27)(28)(29) определены достоверные различия количества пациентов с ограничением констрикторной (р = 0,020) и дилататорной (р < 0,001) функций до и после курения, независимо от способа доставки никотина. Так, нарушение констрикторной функции СМА до курения было выявлено у 32 лиц (71%), а после курения -у 41 человека (91%).…”
Section: Chapter 2 Role Of Endothelial Dysfunction In Development Of ...unclassified
“…It was previously reported that up to 60% of lung cancers were caused by B[ a ]P and other PAHs found in cigarettes, with each cigarette potentially containing 20–40 ng of B[ a ]P. The carcinogenic response could also occur in the bladder, breast, cervix, and prostate . According to a recent clinical study investigating the correlation between smoking and oxidative stress in chronic obstructive pulmonary disease patients, B[ a ]P was the most abundant carcinogenic PAH in smokers and was positively correlated with higher serum uric acid levels . Although lower molecular weight PAHs are predominant in commercial cigarettes, B[ a ]P is used as a representative marker for total PAHs based on the strong positive correlation between them .…”
Section: Polycyclic Aromatic Hydrocarbons (Pahs)mentioning
confidence: 99%